Reprogramming of DNA methylation and changes of gene expression in grafted Hevea brasiliensis - Li, Hui-Liang; Wang, Ying; Guo, Dong; Zhu, Jia-Hong; Wang, Yu; Dai, Hao-Fu; Peng, Shi-Qing (Frontiers in Plant Science, 2024)
Rubber tree (Hevea bralisiensis) is reproduced by bud grafting for commercial planting, but significant intraclonal variations exist in bud-grafted clones. DNA methylation changes related to grafting may be partly responsible for intraclonal variations. In the current study, whole genome DNA methylation profiles of grafted rubber tree plants (GP) and its donor plants (DP) were evaluated by whole genome bisulfite sequencing. Data showed that DNA methylation were down-regulated and DNA methylations in CG, CHG and CHH sequences were reprogrammed in GP, suggesting graft induced reprogramming of DNA methylation. 5,939 differentially methylated genes (DMGs) were identified by comparing fractional methylation levels between GP and DP. Transcriptional analysis revealed that there were 9,798 differentially expression genes (DEGs) in the DP and GP comparison. 1,698 overlapping genes between DEGs and DMGs were identified. These overlapping genes were markedly enriched in the metabolic pathway and biosynthesis of secondary metabolites by KEGG pathway analysis. Global DNA methylation and transcriptional analyses revealed that reprogramming of DNA methylation is correlated with gene expression in grafted rubber tree. The study provides a whole genome methylome of rubber tree and an insight on the molecular mechanisms underlying the intraclonal variations existing in commercial planting grafted rubber trees.